HIPOTESIS SAPIR-WHORF DALAM PROSES TOPONIMI KABUPATEN TUBAN (KAJIAN ANTROPOLOGI LINGUISTIK) - Astrea, Kiki (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2017)
Place naming is a form of linkage of language, culture and thought. This study examines the process of Tuban City naming by finding dialek of Tuban people. In addition, this study also seeks of linkage of language, culture and thought in the process of toponymy of Tuban. Qualitative descriptive approach and informal data presentation methods was used to process and present expected data. Toponymy of Tuban is associated with a figure named Ronggolawe role important to tripe Tuban and finally lifted become the first adipati of Kabupaten Tuban.